International cancer seminars: a focus on esophageal squamous cell carcinoma. (14th June 2017) - Murphy, G.; McCormack, V.; Abedi-Ardekani, B.; Arnold, M.; Camargo, M. C.; Dar, N. A.; Dawsey, S. M.; Etemadi, A.; Fitzgerald, R. C.; Fleischer, D. E.; Freedman, N. D.; Goldstein, A. M.; et al.
Abstract: The International Agency for Research on Cancer (IARC) and the US National Cancer Institute (NCI) have initiated a series of cancer-focused seminars [Scelo G, Hofmann JN, Banks RE et al. International cancer seminars: a focus on kidney cancer. Ann Oncol 2016; 27(8): 1382–1385]. In this, the second seminar, IARC and NCI convened a workshop in order to examine the state of the current science on esophageal squamous cell carcinoma etiology, genetics, early detection, treatment, and palliation, was reviewed to identify the most critical open research questions. The results of these discussions were summarized by formulating a series of 'difficult questions', which should inform and prioritize future research efforts.